Solving load flow solution using evolutionary programming method / Nurul-Huda Ismail - Ismail, Nurul-Huda (2003)
The load flow problem can be expressed a set of nonlinear simultaneous algebraic equations, then it is impossible to have multiple solutions. To overcome the limitations of conventional load flow problem, a genetic based load flow optimisation is developed. This report presents an alternative method for solving the load flow using the evolutionary programming (EP) method. The principal information obtained from a power-flow study is the magnitude and phase angle of the voltage at each bus and the real and reactive power flowing in each line. The EP developed uses the total active and reactive power mismatches as the objective functions for the load flow solution. It is found that the result from the EP are closed to these obtained from the traditional method.